CONSIDERAÇÕES SOBRE A HISTÓRIA DO ENSINO DA LITERATURA INFANTIL NOS CURSOS NORMAIS NO BRASIL: O PIONEIRISMO DE BÁRBARA VASCONCELOS DE CARVALHO - Fernando Rodrigues de Oliveira (Associação Sul-Rio-Grandense de Pesquisadores em História da Educação (ASPHE), 2011)
In order to contribute for de the history of teacher education and the history of teaching children's literature, one presents aspects of professional activity of the teacher Bárbara Vasconcelos de Carvalho and of the development of a research guide that contains textual references of this teacher and about her. The analysis of the results has allowed to understand important aspects about the history of teaching children's literature on elementary teacher education courses in Brazil, specially, the important and pioneering Carvalho role in this history, either by thematizations which she did, through lectures, courses and conferences, either by the materialization of her proposal for the teaching children's literature contained in your children's literature teaching manual.